A Multicenter Cross-sectional Study on the Prevalence and Impact Factors of Hysteria Tendency in the Eastern Chinese Adolescents - Gang ZHAO; Li XIE; Yong XU; Qinglin CHENG (Tehran University of Medical Sciences, 2018)
Background: The aim of this study was to assess the environmental impact-factors differences between female and male HT in the eastern Chinese adolescents. Methods: We used a multicenter, cross-sectional study to estimate the prevalence rates and the associated impact-factors of hysteria tendency (HT) in 2014. Totally, 10131 adolescents took part in the study from three School Health Surveillance System centers in three provinces of east China. The data were collected using a common protocol and questionnaire in order to identify common environment affecting in this population. Results: An overall positive rate of HT among the eastern Chinese adolescents was 13.13% (95% CI: 12.48%-13.80%) with 14.01% (95% CI: 13.05%-15.02%) for females and 12.30% (95% CI: 11.43%-13.22%) for males. Gender-stratified regression analyses revealed that 7 out of the 21 tested covariates were linked to HT only in males, while 9 out of the 21 tested covariates were associated with female HT only. Although, the models pointed out that of all independent variables, the variable -family medical history was the strongest environment impact to both the male HT (amOR=2.49, 95% CI=1.77-3.25) and female HT (amOR=2.83, 95% CI=2.19-3.68). Conclusion: HT is prevalent among adolescents in the eastern Chinese adolescents. Environmental factors differences between female and male HT are significant in adolescents, and HT affects more female than male. First, prevention and therapy of HT in adolescents should focus on various social, school and family environment settings, and individual characteristics. Second, gender -respective intervention programs against HT in adolescents should be implemented.